PROTECTION SYSTEM INI SOLAR PANEL AGAINST INDUCTION MOTOR LOAD - Hadiyanto Hadiyanto; Ali Abrar; Rudiansyah Rudiansyah (Multica Science and Technology (ACCREDITED-SINTA 5), 2025)
Solar Power Plants (PLTS) have become one of the solutions to meet the need for clean and sustainable energy. However, like other electrical systems, PLTS is also susceptible to disturbances and problems that can interfere with its performance and reliability. This study aims to design and build a voltage and current protection system at the PLTS inverter output to protect the 1-phase induction motor from damage due to unstable voltage and current. The protection system used is Over/Under Voltage Protector, and MCB for overvoltage and undervoltage protection and load current limitation, in order to protect electrical equipment connected to the PLTS system. The test results show that the protection system implemented on the Inverter Output can protect against overvoltage above 250 V, undervoltage below 185 V, and overcurrent.where if this happens then the electricity supply to the load will be automatically cut off